An exploration of inclusion through the voices of young people in Secondary School - Simpson, Caroline Ruth (2025)
Inclusion within education is seen as a right for all children and young people (Opertti et al, 2014). However, there appears to be different interpretations of inclusion within the field of research, policy and practice (Goransson & Nilholm, 2014). Within this study inclusion was viewed as the acceptance, participation and achievement of all children and young people (Ainscow et al, 2006). The importance of gathering pupil voice in relation to inclusion is widely acknowledged (Messiou, 2019; Shogren et al, 2015). Children and young people as key stakeholders in inclusion policy and practice can offer unique insights (Shogren et al, 2015) and have the ability to be a catalyst for change (Messiou, 2019). However, children and young people’s perceptions and experiences of inclusion have had very little exploration (Koutsouris et al, 2024). Often research has taken a narrow view of inclusion and focused solely on hearing the voices of specific populations of children with Special Educational Needs and Disabilities (SEND) (Adderley et al, 2015), ignoring that marginalisation and exclusion can occur for many reasons not solely due to SEND (Messiou, 2012). The study aimed to explore the voices of young people in relation to their views and experiences of inclusion in their secondary school. Nine semi-structured interviews were undertaken with students in Years 9 and 10 in a mainstream secondary school in the North of England. The data was analysed through Reflexive Thematic Analysis, using an inductive approach. The findings illustrated six themes; ‘school as a community’, ‘relationships matter’, ‘school systems that promote experiences of inclusion’, ‘social emotional pressures can impact on our inclusion, ‘we all have a role to play’, and ‘unfairness erodes feelings of inclusion’. Following the presentation of the themes, they are discussed in relation to the previous literature and research on inclusion. The methodological limitations are outlined and addressed. Potential implications for schools, Educational Psychologists (EPs), Local Authorities (LAs) and Government are presented, alongside possible future research.